Given:
![f(x)=2 x^(2)+6](https://img.qammunity.org/2021/formulas/mathematics/college/tqowo3rowy07d71t3ei38da2rkkjq8oclq.png)
To find:
The average rate of change.
Solution:
Average rate of change formula:
![$(f(b)-f(a))/(b-a)](https://img.qammunity.org/2021/formulas/mathematics/college/x902cz29ha7kuduq0q26ngbc5klkswe2d7.png)
(a) Average rate of change from 2 to 4:
Substitute x = 4 and x = 2 in f(x).
![$(f(4)-f(2))/(4-2)=((2(4)^2+6)-(2(2)^2+6))/(4-2)](https://img.qammunity.org/2021/formulas/mathematics/college/bh7gg7ol47t94qlzjbsem1z13s1da89m2j.png)
![$=(38-14)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/wqk1addfuhyccbae06u6tklex8z9ea1lj7.png)
= 12
Average rate of change from 2 to 4 is 12.
(b) Average rate of change from 1 to 3:
Substitute x = 3 and x = 1 in f(x).
![$(f(3)-f(1))/(3-1)=((2(3)^2+6)-(2(1)^2+6))/(3-1)](https://img.qammunity.org/2021/formulas/mathematics/college/x5pa6hoa96y9e72lgcddjpzvwldsaeetdt.png)
![$=(24-8)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/hcibwzh5f1erab45gv0se17b5pev58ue92.png)
= 8
Average rate of change from 2 to 4 is 8.
(c) Average rate of change from -2 to 1:
Substitute x = 1 and x = -2 in f(x).
![$(f(1)-f(-2))/(1-(-2))=((2(1)^2+6)-(2(-2)^2+6))/(1+2)](https://img.qammunity.org/2021/formulas/mathematics/college/kny3xsaxahmim7zz3hago1aec0pokbo7bw.png)
![$=(8-14)/(3)](https://img.qammunity.org/2021/formulas/mathematics/college/25h0p2ixxz33xz6ej4vo29h1f3yvjzqcbw.png)
= -2
Average rate of change from 2 to 4 is -2.